2004
DOI: 10.1111/j.0022-1112.2004.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

A non‐invasive stress assay based upon measurement of free cortisol released into the water by rainbow trout

Abstract: A procedure previously used for sex steroids was adapted to extract free cortisol and cortisone from water samples taken from rainbow trout Oncorhynchus mykiss tanks. Both corticosteroids could be readily detected by radioimmunoassay (RIA), with cortisol being predominant. All stages of the sampling, extraction and RIA procedure were validated for cortisol. An intermittent problem with poor replication was traced to the use of diethyl ether during the extraction procedure, and was overcome by the use of ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
3
30

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(255 citation statements)
references
References 37 publications
13
209
3
30
Order By: Relevance
“…In reef fishes (Chromis dimidiatus and Pseudanthias squamipinnis), it was observed that the F levels measured in water correlated with the social situations of these fish, with higher excretion levels in more stressed fish (Oliveira et al, 1999). In rainbow trout, there was a positive correlation between stress situation, F release in water and F levels in plasma (Ellis et al, 2004).…”
Section: Hormone Assaysmentioning
confidence: 91%
See 2 more Smart Citations
“…In reef fishes (Chromis dimidiatus and Pseudanthias squamipinnis), it was observed that the F levels measured in water correlated with the social situations of these fish, with higher excretion levels in more stressed fish (Oliveira et al, 1999). In rainbow trout, there was a positive correlation between stress situation, F release in water and F levels in plasma (Ellis et al, 2004).…”
Section: Hormone Assaysmentioning
confidence: 91%
“…Fish release several fractions of steroid hormones into the water; the free fraction is mainly released through the gills, the conjugated fractions through urine (sulphated fraction) and faeces (glucuronidated fraction) (Scott and Sorensen, 1994;Vermeirssen and Scott, 1996;Ellis et al, 2004). The hormone measurements were carried out following the procedures to measure steroids from fish holding water described by Scott and Sorensen (1994) and from fish urine described by Oliveira et al (1996).…”
Section: Hormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots of pooled rainbow trout plasma were used as quality controls (QCs) and the intra-and inter-specific assay coefficients of variation were 2.1-3.7 % and 5.5 %, respectively. Cortisol was assayed by radioimmunoassay previously described by Ellis et al (2004) and modified by North et al (2006). Aliquots of pooled rainbow trout plasma were used as quality controls (QCs) and the intraspecific assay coefficients of variation was 4.2 %.…”
Section: Hormonal Assaysmentioning
confidence: 99%
“…For example, indwelling catheters might provide very accurate data on the stress response experienced by an individual fish but this does not provide information that is valuable at the level of the population. Assays based on water cortisol levels have considerable potential to produce valuable population level data but these are not yet practicable (Ellis et al 2004). Therefore, we are restricted to point-source samples of cortisol and it is arguable whether such samples provide any valuable insight into the welfare state of the fish.…”
Section: Assessing Fish Welfarementioning
confidence: 99%